1998
DOI: 10.1063/1.121390
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of unidirectional liquid-crystal alignment on polyimides with linearly polarized ultraviolet light exposure

Abstract: Unidirectional liquid-crystal ͑LC͒ alignment by a linearly polarized ultraviolet light ͑UV͒ exposure was examined using two types of polyimide ͑PI͒. PI with a fluorene unit incorporated in a side chain showed LC alignment perpendicular to those of conventional PIs, i.e., perpendicular to the rubbing direction and parallel to the exposure polarization of UV. The results of the dichroic ratio measurement of LC cells, UV absorption spectra, birefringence, infrared absorption spectra, and PI conformation calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…In past years, this technique has been extensively used to align LC materials. [109][110][111][112] Recently, Chou et al demonstrated that this approach can also be applied to aligning small conjugated molecules, thereby fabricating OFETs with anisotropic electronic properties. [49] As shown in Figure 13a, on a photoaligned polyimide layer, the pentacene film is aligned perpendicularly to the polarization direction of the incident UV light, resulting in grains continuous along this direction.…”
Section: Alignment Layers Prepared By Photoirradiationmentioning
confidence: 98%
“…In past years, this technique has been extensively used to align LC materials. [109][110][111][112] Recently, Chou et al demonstrated that this approach can also be applied to aligning small conjugated molecules, thereby fabricating OFETs with anisotropic electronic properties. [49] As shown in Figure 13a, on a photoaligned polyimide layer, the pentacene film is aligned perpendicularly to the polarization direction of the incident UV light, resulting in grains continuous along this direction.…”
Section: Alignment Layers Prepared By Photoirradiationmentioning
confidence: 98%
“…The irradiation of the film surface with linearly polarized UV light is a promising alternative. [6,9,10] The orientation of a polymer doped with an azo dye has been reported, however, it suffered from limited light stability. Later, stable photoinduced liquid-crystal (LC) alignment layers of more advanced materials, such as cinnamoyl side-chain polymers [11] or polyimides, [12] were introduced.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental design is similar to methods for measuring the azimuthal anchoring energy of liquid crystals on treated substrates [19]. The mechanism of liquid crystal alignment induced by a rubbed polymer layer itself is the subject of much study but is thought to include physical grooves, aligned polymer chains, and the van der Waals torque for surfaces in contact [20][21][22][23]. The last of these is equivalent to the short-ranged Casimir torque of our proposed study, though distinguishing the van der Waals effect from other alignment effects is difficult.…”
Section: Introductionmentioning
confidence: 99%